LKPD Berbasis Pembelajaran Saintirik pada Pembelajaran Tematik tema Kayanya Negeriku dI Kelas IV SD - Fadhlina, Ariska Putri; Sukmawarti, Sukmawarti (JURNAL PENELITIAN PENDIDIKAN MIPA, 2024)
This study aims to develop scientifically based LKPD on thematic learning of the theme of Kayanya Negeriku which is suitable for use in the learning process in class IV SD. In this study the researchers used a Research and Development (R&D) research design. Research and development is carried out using the 4D development model developed by Thiagarajan, namely (1) Define, (2) Design, (3) Development, and (4) Dissemination. However, in this study the 4D stage was carried out only up to stage 3, namely Development. The subjects in this study were LKPD reviewers and material reviewers. The object in this study is the Scientific Based Worksheet on Thematic Learning on the Kayanya Negeriku Theme which is suitable for use in the thematic learning process in class IV. The instruments and data collection techniques used in this study were questionnaires. The questionnaire used in this study was in the form of a validation questionnaire given to LKPD expert validators and material experts. The validation results from LKPD experts obtained a score of 81.4 and from the validation of material experts obtained a score of 83.6. From this score it can be said that the scientific-based LKPD on thematic learning theme 9 "My Rich Country" which was developed "Very Feasible" for use in the learning process.